Entangling two spin ensembles in diamond nanostructures via a superconducting flux qubit. (9th June 2015) - Ma, Yong-Hong; Zhang, Xue-Feng
Abstract: Entanglement between macroscopic systems is a basic resource for many quantum information processing, and so it is crucially important to investigate the possibility of achieving entanglement between macroscopic systems. In this work, we propose a novel mechanism for achieving entanglement between two spin ensembles in diamond nanostructures. The interaction between two spin ensembles, associated with the nitrogen-vacancy centers in diamond, are mediated by their coupling with a flux qubit. Using numerical methods, we show that two spin ensembles are entangled with the time evolution under realistic experimental conditions. This macroscopic entanglement between two spin ensembles has important implications for ongoing efforts to realize quantum computation and communication.